Prediction of the Ultra-Large Container Ships' Propulsion Power at the Initial Design Stage - Korlak, Piotr Kamil (Communications - Scientific Letters of the University of Zilina, 2022)
Container ships represent the fastest growing segment of maritime transport. The need to reduce unit transportation costs and environmental impact has led to development of the most capacious ultra-large container ships operating on the world's major shipping routes. A representative database of ultra-large container ships was created and further subdivided according to the main technical parameters. Using a simple cubic regression model, based on the least squares method, an equation, compliant to the general propeller law, was developed to predict the propulsion power of ultra-large container ships as a function of their sailing speed. The results obtained using the developed equation should be sufficiently close to the results of the exact verification calculations at the technical design stage. Then this prediction would find application in the design of both main propulsion, as well as waste heat and cold recovery systems.
Keywords: container ship; ULCS; ULCV; ship design; ship propulsion; low-speed engine; two-stroke engine